The study of factors affecting on COSO ERM success and its consequences: an empirical research of Thai-listed companies - Tontiset, Nattawut (Business: Theory and Practice, 2025)
The goal of this study was to look at the causes and effects of the COSO ERM success of the companies listed on the Thai Stock Exchange. The internal resources and capabilities including effective AIS design, top management support, and internal auditor competency are assumed to become the antecedents of COSO ERM success. Moreover, the consequences of COSO ERM success are sustainable value creation, achieve strategy and goal, promote efficiency and effectiveness, financial reporting quality, and compliance with law. Thai-listed firms were used as research subjects, and data from the chief internal control was collected via a mail survey process and a questionnaire. The overall findings show that successful COSO ERM is influenced positively and significantly by effective AIS design, top management support, and internal auditor competency. Additionally, the achievement of strategy and goals, promotion of efficiency and effectiveness, quality of financial reporting, and legal compliance are all positively impacted by COSO ERM success. Moreover, achieve strategy and goal, promote efficiency and effectiveness, financial reporting quality, compliance with law all have a positive, significant impact on the creation of sustainable value. Overall, the results demonstrate that excellent AIS design, top management backing, and internal auditor expertise are required for a company to develop both COSO ERM success and long-term sustainable value generation.